$[(-3 + 5) × 2]^2 - 10 = 6$ $4 × [(-2)^2 - 6 ÷ 3] = 8$ $-2 × [3 + (-1)^3 × 4] = 2$ $[5 - (8 ÷ 2)]^2 + (-4) = -3$ $[(7 - 9) × (-3)] + 2^3 = 14$ $-4 ÷ [2 + (-5 + 4)] = -4$ $[(-1)^4 × 6] - (15 ÷ 3) = 1$ $3 × [(-2)^3 + 4] - 7 = -19$ $[12 ÷ (-4) + 5]^2 - 9 = -5$ $[-5 + 2 × (-3)]^2 ÷ 11 = 11$
$2 × [(-4)^2 - 10 ÷ 5] = 28$ $[(-5 + 2) × 3]^2 - 15 = 66$ $-3 × [4 + (-2)^3 × 2] = 36$ $[6 - (9 ÷ 3)]^2 + (-7) = 2$ $[(1 - 3) × (-4)] + 3^3 = 35$ $-6 ÷ [3 + (-7 + 5)] = -6$ $[(-2)^4 × 2] - (20 ÷ 4) = 27$ $4 × [(-3)^3 + 5] - 8 = -96$ $[15 ÷ (-5) + 6]^2 - 12 = -3$ $[-8 + 3 × (-2)]^2 ÷ 49 = 4$
$-2 × [4 + (-1)^3 × 5] = 2$ $[(6 - 8) × (-2)]^2 + 3^3 = 43$ $[(-3 + 7) × 2]^2 - 14 = 50$ $5 × [(-3)^2 - 12 ÷ 4] = 30$ $-4 ÷ [4 + (-9 + 6)] = -4$ $[(-1)^5 × 8] - (25 ÷ 5) = -13$ $[8 - (12 ÷ 4)]^2 + (-5) = 20$ $4 × [(-2)^3 + 6] - 9 = -17$ $[(2 - 6) × (-3)] + 4^2 = 28$ $[18 ÷ (-6) + 7]^2 - 10 = 6$
$-3 × [5 + (-2)^2 × 2] = -39$ $[(4 - 9) × (-3)] + 2^4 = 31$ $[14 ÷ (-7) + 8]^2 - 11 = 25$ $[-7 + 2 × (-4)]^2 ÷ 25 = 9$ $3 × [(-3)^2 - 8 ÷ 2] = 15$ $[(-6 + 3) × 4]^2 - 20 = 124$ $-5 ÷ [5 + (-8 + 4)] = -5$ $[(-2)^4 × 3] - (30 ÷ 6) = 43$ $[9 - (15 ÷ 5)]^2 + (-6) = 30$ $5 × [(-1)^3 + 7] - 13 = 17$
$[-9 + 4 × (-2)]^2 ÷ 17 = 17$ $4 × [(-4)^2 - 14 ÷ 7] = 56$ $[(5 - 7) × (-5)] + 3^3 = 37$ $-2 × [6 + (-2)^3 × 3] = 36$ $[10 - (16 ÷ 8)]^2 + (-8) = 56$ $[(-1)^6 × 9] - (35 ÷ 7) = 4$ $6 × [(-2)^2 + 3] - 16 = 26$ $[-6 + 3 × (-3)]^2 ÷ 9 = 25$ $[24 ÷ (-8) + 9]^2 - 15 = 21$ $2 × [(-5)^2 + 100] ÷ 10 = 25$